1994
DOI: 10.1002/eji.1830240203
|View full text |Cite
|
Sign up to set email alerts
|

The envelope glycoprotein of HIV‐1 gp120 and human complement protein C1q bind to the same peptides derived from three different regions of gp41, the transmembrane glycoprotein of HIV‐1, and share antigenic homology

Abstract: gp41, the transmembrane glycoprotein of HIV-1, has been shown to be non-covalently associated with gp120. We have shown that it also binds human C1q. To analyze the interaction site(s) of gp41 with these two molecules, we established an enzyme-linked immunosorbent assay (ELISA) system using recombinant soluble gp41 [amino acids (aa) 539-684] and peptides thereof. In the cell-external part of gp41 three sites (aa 526-538, aa 590-613 and aa 625-655) were found to bind both gp120 and C1q. That gp120 and C1q use t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…This possibility was strongly supported by the observations of Stoiber et al (12) on the functional and structural similarities of C1q and gp120, the external glycoprotein of HIV-1. The two proteins were found to compete for the same binding sites on gp41 (12). In addition, rabbit antibod-ies to human C1q recognized gp120 and rabbit antibodies to gp120 cross-reacted with C1q (12).…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…This possibility was strongly supported by the observations of Stoiber et al (12) on the functional and structural similarities of C1q and gp120, the external glycoprotein of HIV-1. The two proteins were found to compete for the same binding sites on gp41 (12). In addition, rabbit antibod-ies to human C1q recognized gp120 and rabbit antibodies to gp120 cross-reacted with C1q (12).…”
Section: Introductionmentioning
confidence: 75%
“…The two proteins were found to compete for the same binding sites on gp41 (12). In addition, rabbit antibod-ies to human C1q recognized gp120 and rabbit antibodies to gp120 cross-reacted with C1q (12). Based on these results, Stoiber et al (12) postulated the possibility of development of C1qAb in HIV infection and found nine sera from HIV-infected subjects to agglutinate erythrocytes coated with antibody and C1q (EAC1q).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…17 Moreover, the HIV-1 surface proteins gp41 and gp120 further enhance Ab-mediated complement activation by binding C1q or MBL, respectively. [18][19][20][21][22][23][24][25] Using serum from an uninfected C1q-or C3-deficient individual as a source of complement does not mediate any anti-HIV-1 activity, which indicates that the classical pathways contribute mainly to the complement activation against HIV-1. 26 Several reports demonstrate that complement-dependent virus lysis occurs in vivo 27,28 and that the complement can enhance the effect of neutralizing Ab both in vivo and in vitro.…”
Section: Protective Role Of Complement Activation and Ab Immunity In mentioning
confidence: 99%